2010
DOI: 10.1038/jid.2009.309
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Intramolecular Epitope Spreading of Humoral Responses to Human BPAG2 in a Transgenic Model

Abstract: Bullous pemphigoid (BP) is a subepidermal autoimmune disease characterized by a humoral response to an epidermal basement membrane (BM) component, BP antigen 2 (BPAG2). BP patients have IgG autoantibodies against an immunodominant BPAG2 extracellular domain termed NC16A as well as additional epitopes located both in the intracellular and extracellular domains (ICD and ECD, respectively) of this autoantigen. To study the evolution of humoral responses to BPAG2, sequential serum samples obtained from C57BL/6Ncr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…IgG spreading from BP180 to BP230 might be attributed to the physical interaction between the NH2-terminal portions of BP230 and BP180 . These findings are in line with a previous study aimed at investigating the dynamics of the IgG response against human BP180 in a mouse model, in which transgenic mouse skin expressing human BP180 was grafted on wild-type animals (Di Zenzo et al, 2010). These mice developed first IgG against extracellular BP180 epitopes and thereafter IgG binding to intracellular epitopes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…IgG spreading from BP180 to BP230 might be attributed to the physical interaction between the NH2-terminal portions of BP230 and BP180 . These findings are in line with a previous study aimed at investigating the dynamics of the IgG response against human BP180 in a mouse model, in which transgenic mouse skin expressing human BP180 was grafted on wild-type animals (Di Zenzo et al, 2010). These mice developed first IgG against extracellular BP180 epitopes and thereafter IgG binding to intracellular epitopes.…”
Section: Discussionsupporting
confidence: 90%
“…In this model, IgG reactivity with extracellular epitopes preceded IgG recognition of intracellular domain. Appearance of IgG autoantibodies directed against intracellular epitopes correlated with the development of graft loss (Di Zenzo et al, 2010). A recent study that utilized a vast array of BP230 and BP180 peptides strongly suggested that BP patients have a specific IgG autoantibody profile, including IgG recognition of intracellular epitopes, which is detectable already at an early stage of the disease (Di Zenzo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is highly likely that autoantibodies targeting both pathogenically relevant epitopes, resulting from intramolecular epitope spreading, could have additive pathogenic effects. Indeed, in mouse models of bullous pemphigoid, intramolecular epitope spreading is found to be highly correlated with clinical symptoms [47].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of those autoantibodies has not been elucidated, although intramolecular epitope spreading has been advocated to explain the development of these autoantibodies (20)(21)(22).…”
mentioning
confidence: 99%